Hydraulic Pressure Ripple Energy Harvesting: Structures, Materials, and Applications (Adv. Energy Mater. 9/2022). Issue 9 (3rd March 2022) - Xiao, Huifang; Pan, Min; Chu, Jun Yu Harry; Bowen, Chris R.; Bader, Sebastian; Aranda, Javier; Zhu, Meiling
Abstract : Hydraulic Pressure Energy In article number 2103185, Chris R. Bowen and co‐workers present a comprehensive overview of the state‐of‐the‐art in hydraulic pressure energy harvesting, which includes the fundamentals of pressure ripples in hydraulic systems, and the selection of electroactive materials and device structures. In addition, novel approaches for improving the harvested energy and potential applications for the technology are discussed, and future research directions are proposed and outlined.